Mythmaking of romantic love relationships in Filipino love team films - Roy, Juan Miguel A. 1990-; Tabora, Kevin B.
"This study aimed to unravel the myths on romantic love relationships in Filipino love team films and its evolution from the 1970s to the 2000. This study involved analyzing eight films all in all, with two films representing each decade. Each film was deconstructed according to their characters' socio demographic backgrounds, physical appearances and personality traits as well as the film's narrative structure which included the events taking place throughout the narrative progression. The theories of Barthes, Levi-Strauss, and Greimas of narrative semiotics were utilized for this study. All their theories have been synthesized and used as a model to read, deconstruct and analyze the films chosen. Poverty or socio economic differences are the overarching problems involved in these films. Almost all the films analyzed involved stories with overs coming from different socio economic classes. Other problems that have been unraveled were those of love triangles, miscommunication, and career. The films provided solutions to these problems in the context of the developing romantic love relationship of the couples. By unraveling these myths, the researchers believed that audiences may become aware of and more critical of the messages conveyed in these types of films."